From Doubt to Conviction: Exploring New Muslims’ Engagement with Sunnah-Based Proofs of Prophethood - Ibrahim Elshahat Mohamed Khamis (Al-Bayān, 2025)
This study investigates how new Muslims engage with Sunnah-based rational proofs of Prophet Muhammad’s (PBUH) prophethood - particularly through the frameworks of Shamae’l (his noble characteristics) and Dalae’l An-Nubuwah (evidence of prophethood). Departing from previous research focused on preachers’ strategies, this paper centers the voices of 30 new Muslims at the Islamic Information Center-Dubai to understand how these proofs influence belief, conviction, and identity transformation. Using Creswell’s qualitative methodology, the study analyzes in-depth interviews through open, axial, and thematic coding. The findings reveal two intersecting domains: the effectiveness of structured Sunnah-based evidence, and the lived spiritual and psychological journeys of new Muslims. Rational proofs such as the Prophet’s moral excellence and the Qurʾan’s intellectual depth often resolved long-standing theological doubts. Emotional triggers, inner spiritual dissatisfaction, admiration for Muslim conduct, and moments of personal transformation emerged as critical themes The study underscores the unique power of combining rational argumentation with experiential authenticity. It recommends audience-sensitive, Sunnah-rooted Dawah approaches that recognize the diverse motivations and challenges faced by new Muslims - bridging reason and heart in the journey from doubt to conviction.